Acute myocardial infarction after a negative Dobutamine stress echocardiogram in a patient with end-stage liver disease - Ahmad, Khursheed; Shahzad, Khurram; Muhammad Muzaffar Mahmood (Journal of the Pakistan Medical Association, 2023)
Dobutamine stress echocardiogram (DSE) is generally a safe and reliable test for detection of myocardial ischaemia. We report the case of a 43-year-old male with end-stage liver disease (ESLD), who underwent DSE as part of workup for liver transplantation. Although the patient had an uneventful negative DSE, within 45 minutes he developed inferior ST-segment elevation myocardial infarction (STEMI). His coronary angiography showed severe 2-vessel coronary artery disease, which was treated with percutaneous coronary intervention (PCI) with implantation of drug-eluting stents (DES). Acute coronary syndrome (ACS) after a normal DSE has previously been reported in the literature. We describe one such case, with added complexity of managing an ACS in a patient with high bleeding risk. Our case is unique in reporting a STEMI after a negative DSE in a liver transplant recipient. Increased physician awareness of potential complications of DSE is essential to allow timely recognition and management.